Studies of the effects of shear on colloidal aggregation and gelation using small angle light scattering - Mokhtari, Tahereh (Kansas State University, 2007)
We investigated the effect of shear on the structure and aggregation kinetics of unstable colloids using small angle light scattering. We used an aqueous suspension of 20 nm polystyrene latex microspheres and MgCl[subscript]2 to induce aggregation. The sample was only sheared once for approximately 33 sec at different times, typically 1 min, 5 min, or 15 min, after the onset of aggregation. The average shear rate was in the range of 0.13 - 3.56 sec[superscript]−1 , which was in a laminar regime. The unsheared sample gelled after ca. 45 min. When the sample was sheared soon after the onset of aggregation, the aggregation followed the diffusion limited cluster cluster aggregation (DLCA) kinetics to yield D[subscript f] = 1.80 [plus or minus] 0.04 aggregates unaffected by the shear. The gel time also remained the same as the unsheared gel. Shearing at later stages of aggregation shortened the gel time and enhanced the scattered light intensity significantly indicating rapid growth. Then, depending on the shear rate, there were three different behaviors. At high shear rates, the aggregate structure was inhomogeneous after the shear was stopped with a crossover in slope in the scattered light intensity versus q, to imply hybrid superaggregates with two different fractal dimensions. At intermediate shear rates far from the gel point, there was a similar crossover after the shear was stopped; however, the fractal dimension regained 1.80 [plus or minus] 0.04 at the gel point. At low shear rates, the aggregation rate was increased, but the aggregate structure was uniform, and the fractal dimension remained 1.75 [plus or minus] 0.05.
Keywords: Light Scattering; Aggregation; Shear; Gelation; Physics, Condensed Matter (0611)